Sistem Proteksi Motor Induksi 3 Fasa Terhadap Bermacam Gangguan Menggunakan Mikrokontroller - Darmawansyah, Darmawansyah; Rosa, M Khairul Amri; Anggraini, Ika Novia (UNIB Press, 2020)
ABSTRACTIn the current era of globalization, various human jobs depend on electrical equipment such as three-phase induction motors. Three-phase induction motors are very important to use according to their roles and functions. The occurrence of voltage variations in the electric power system is due to the magnitude of the voltages between the three phases which are not the same so that there are differences in the angle of the R, S and T phases, which causes an uneven load overload in the electrical distribution system. Among the disturbances that can occur are overvoltage, under voltage, unbalance voltage between phases, overload, and overheating. Based on these problems, a three-phase induction motor protection system was designed, the system uses current, voltage, temperature sensors, which functions to measure the value when a disturbance occurs, a magnetic contactor as a breaker and a liaison when the disturbance is given in accordance with the set point value given to the microcontroller. The results of the research for unbalanced voltage of V1 112 V, V2 114 V, V3 108 V, overvoltage of V1 228 V, V2 207 V, V3 264 V, over current of A1 104 A, A2 107 A, A3 0.77 A , the overload on the resistance source is 333 ?, 250 ?, 200 ?, 167 ?, and the overheating is 40.75 ºC at 6.5 minutes with tripping conditions in each test. The final results of this study indicate that the protection system which is designed is better used for three-phase induction motors.Keywords: unbalaced, disturbances, protection systems, sensors, magnetic contactor, microcontroller.